2017
DOI: 10.1177/0363546517741704
|View full text |Cite
|
Sign up to set email alerts
|

Hip Distraction Without a Perineal Post: A Prospective Study of 1000 Hip Arthroscopy Cases

Abstract: The use of the Trendelenburg position and a specially designed distraction setup during hip arthroscopy allows for safe hip distraction without a perineal post, thereby eliminating groin-related soft tissue and nerve complications. Certain patient variables can be used to estimate the required distraction force and inclination angle with this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 40 publications
1
84
0
1
Order By: Relevance
“…All patients underwent hip arthroscopy under general anesthesia. Hip arthroscopy was performed without a perineal post, as described previously, 20 , 32 on a specially designed hip arthroscopy distraction apparatus in the standard supine and in an 11° to 15° Trendelenburg position to allow access to the affected hip. Additionally, fluid pressure utilized during the procedure was maintained at ≤30 mm Hg to reduce soft tissue fluid extravasation (20-25 mm Hg during central compartment work and 25 mm Hg in >95% of cases during peripheral compartment work, with <5% of cases at 25-30 mm Hg during peripheral compartment work).…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent hip arthroscopy under general anesthesia. Hip arthroscopy was performed without a perineal post, as described previously, 20 , 32 on a specially designed hip arthroscopy distraction apparatus in the standard supine and in an 11° to 15° Trendelenburg position to allow access to the affected hip. Additionally, fluid pressure utilized during the procedure was maintained at ≤30 mm Hg to reduce soft tissue fluid extravasation (20-25 mm Hg during central compartment work and 25 mm Hg in >95% of cases during peripheral compartment work, with <5% of cases at 25-30 mm Hg during peripheral compartment work).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Mei-Dan et al which reported on 309 hips operated on using this technique found that the mean Trendelenburg angle was 11° ± 2° and that the patient variables determining distraction force were sex, weight, and lateral center edge angle (LCEA). [14] Males, heavier individuals, and those with a high LCEA required a higher distraction force. Further studies of post-less HA use ordinary equipment to achieve distraction, while sustaining low costs, demonstrating increasing accessibility of this technique.…”
Section: Advances Alternatives To Perineal Postmentioning
confidence: 95%
“…All patients underwent hip arthroscopy without a perineal post [ 29 ] prior to PAO/DFO in order to address intra-articular hip pathology such as labral tears, chondral damage, cam lesions and/or LT tendinopathy. The osteotomy procedure was performed 7–14 days following arthroscopy.…”
Section: Methodsmentioning
confidence: 99%